2006
DOI: 10.1152/ajprenal.00386.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the epithelial Na+ channel (ENaC) by phosphatidylinositides

Abstract: The epithelial Na ϩ channel (ENaC) is an endeffector of diverse cellular signaling cascades, including those with phosphatidylinositide second messengers. Recent evidence also suggests that in some instances, phospatidylinositides can directly interact with ENaC to increase channel activity by increasing channel open probability and/or membrane localization. We review here findings relevant to regulation of ENaC by phosphatidylinositol 4,5-bisphosphate (PIP 2) and phosphatidylinositol 3,4,5-triphosphate (PIP3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 100 publications
(177 reference statements)
3
68
0
Order By: Relevance
“…These studies indicate that ROS may stimulate PI3K and consequently promote the synthesis of PI(3,4,5)P 3 . We (18 -20) and others (21,22) have previously shown that PI(3,4,5)P 3 stimulates ENaC. Taken together, these studies suggest that H 2 O 2 may stimulate ENaC by elevating PI(3,4,5)P 3 through activation of PI3K.…”
Section: Enacsupporting
confidence: 61%
“…These studies indicate that ROS may stimulate PI3K and consequently promote the synthesis of PI(3,4,5)P 3 . We (18 -20) and others (21,22) have previously shown that PI(3,4,5)P 3 stimulates ENaC. Taken together, these studies suggest that H 2 O 2 may stimulate ENaC by elevating PI(3,4,5)P 3 through activation of PI3K.…”
Section: Enacsupporting
confidence: 61%
“…These include extracellular cations (H ϩ , Na ϩ , and other metals), anions (Cl Ϫ ), laminar shear stress, and proteases that cleave ENaC subunits at specific sites and release embedded inhibitory tracts (1, 2, 9 -14). Intracellular phosphorylation, inositol phospholipids, and cytoplasmic Cys palmitoylation also regulate ENaC P o (15)(16)(17)(18)(19)(20)(21).…”
Section: Enacsmentioning
confidence: 99%
“…115,116 Interestingly, phosphatidylinositol 3-kinase influences both ENaC trafficking (through SGK1 and/or Akt) and P o . 117 These myriad signaling pathways demonstrate a complex regulatory network that directly and indirectly influences ENaC surface expression and P o . Such mechanisms are likely operative in acute, subacute, and chronic changes in ENaC regulation.…”
Section: Namentioning
confidence: 99%